Aging, inflammation, immunity and periodontal disease. Issue 1 (October 2016) - Ebersole, Jeffrey L.; Graves, Christina L.; Gonzalez, Octavio A.; Dawson, Dolph; Morford, Lorri A.; Huja, Pinar Emecen; Hartsfield, James K.; Huja, Sarandeep S.; Pandruvada, Subramanya; Wallet, Shannon M.
Abstract: The increased prevalence and severity of periodontal disease have long been associated with aging, such that this oral condition affects the majority of the adult population over 50 years of age. Although the immune system is a critical component for maintaining health, aging can be characterized by quantitative and qualitative modifications of the immune system. This process, termed 'immunosenescence', is a progressive modification of the immune system that leads to greater susceptibility to infections, neoplasia and autoimmunity, presumably reflecting the prolonged antigenic stimulation and/or stress responses that occur across the lifespan. Interestingly, the global reduction in the host capability to respond effectively to these challenges is coupled with a progressive increase in the general proinflammatory status, termed 'inflammaging'. Consistent with the definition of immunosenescence, it has been suggested that the cumulative effect of prolonged exposure of the periodontium to microbial challenge is, at least in part, a contributor to the effects of aging on these tissues. Thus, it has also been hypothesized that alterations in the function of resident immune and nonimmune cells of the periodontium contribute to the expression of inflammaging in periodontal disease. Although the majority of aging research has focused on the adaptive immune response, it is becoming increasingly clear that the innate immune compartment is also highly affected by aging. Thus, the phenomenon of immunosenescence and inflammaging, expressed as age‐associated changes within the periodontium, needs to be more fully understood in this era of precision and personalized medicine and dentistry.